A dictionary of Arabic and Islamic proverbs - Lunde, Paul 1943-; Wintle, Justin 1949- (Routledge & Kegan Paul, 1984)
One of the quickest ways to understand a people or a culture is to learn their proverbs. This anthology, first published in 1984, compiles in dictionary form proverbs from the Islamic world, particularly the Middle East and North Africa. The Arabs were the first to gather and annotate their own proverbs - the earliest collections date from the n